PARADIGMA HUKUM ISLAM KLASIK DAN ALTERNATIF - Mohamad Ikrom (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2019)
Islam is a universal religion, there is no limitation of place and time, therefore Islam should be accepted by every human being on this earth, without having to have